Analysis of The Meanings of Prepositions In Surat Al-Sajadah - Arifin, Zainal; Mustaqim, Mustaqim; Mukit, Abdul; Kholik, Abd (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar, Pamekasan, 2023)
Surat Al-Sajdah from one of the chapters that was found in the twenty-fourth volume. It has ninety-six, and it is Makkah al-Nuzul, and it contains many prepositions that have different meanings, and they need to be researched to know the meanings of the guaranteed verse. Knowing the meanings of prepositions has a strong relationship with the meanings of profanity and the word. As for the research methodology, this research is some of the types of library research. What is meant by library research is the research in which the researcher works in or outside the library for all facts or data from the types of books. As for the result that the researcher found in this study about the verses that contain prepositions in Surat Al-Sajdah, they are the letter “from” and the letter “lam” and the letter “in” and the letter “baa” and the letter “to” and the letter “on” and the letter “a.” It has different meanings such as a statement of gender, superfluous, adverbial, substituting the beginning of the purpose in place, metaphorical spatial circumstance, circumstantial real time, circumstantial real spatial, supremacy, simile, causation, concomitant, transcendent metaphorical supremacy.